Evaluating the Vector Control Potential of the In2Care® Mosquito Trap Against Aedes aegypti and Aedes albopictus Under Semifield Conditions in Manatee County, Florida - Buckner, Eva A; Williams, Katie F; Marsicano, Ambyr L; Latham, Mark D; Lesser, Christopher R (Journal of the American Mosquito Control Association, 2017)
Successful integrated vector management programs may need new strategies in addition to conventional larviciding and adulticiding strategies to target Aedes aegypti and Ae. albopictus, which can develop in small, often cryptic, artificial and natural containers. The In2Care® mosquito trap was recently developed to target and kill larval and adult stages of these invasive container-inhabiting Aedes mosquitoes by utilizing autodissemination. Gravid females that visit the trap pick up pyriproxyfen (PPF) that they later transfer to nearby larval habitats as well as Beauveria bassiana spores that slowly kill them. We assessed the efficacy of the In2Care mosquito trap in a semifield setting against locally sourced strains of Ae. aegypti and Ae. albopictus. We found that the In2Care mosquito trap is attractive to gravid Ae. aegypti and Ae. albopictus females and serves as an egg sink, preventing any adult emergence from the trap (P = 0.0053 for both species). Adult females successfully autodisseminated PPF to surrounding water-filled containers, leading to a statistically significant reduction in new mosquito emergence (P ≤ 0.0002 for both species). Additionally, we found effective contamination with Beauveria bassiana spores, which significantly reduced the survivorship of exposed Ae. aegypti and Ae. albopictus (P ≤ 0.008 for both species in all experimental setups). In summary, the In2Care mosquito trap successfully killed multiple life stages of 2 main mosquito vector species found in Florida under semifield conditions.